The auditor’s qualifications and their role in the quality of professional performance - ابراهيم لبنى زيد; سبتي محمد سالم (Journal of Economics and Administrative Sciences, 2019)
Abstract The aim of the research is to clarify the requirements of the qualification of the external auditor in Iraq and the extent of their impact on the quality of the professional performance of the audit process. The research was based on analyzing the results of the questionnaire prepared for the impact of qualifications on the quality of professional performance. The researcher has reached a number of conclusions, the most important of which is that a highly qualified and unethical auditor has a greater negative impact on the quality of professional performance than those with low qualifications. The most important recommendations of the research were the need to pay attention to scientific and vocational rehabilitation, especially the auditing of modern systems that require special skills, because it has an effective effect in improving professional competence through modern sources and techniques, and the latest versions of international professional organizations in teaching and keeping abreast of the curricula of modern developments in the profession and the adoption of subjects Which are taught at international institutes and assisted by professors with practical experience